To assess the cell lines on esophagogastroduod enoscopies of children with feeding difficulty, esophageal fistula and asthma with histologic abnormality: To assess the cell lines on EGD of children - Li, Jun; Yang, Shixiong (Cellular and Molecular Biology, 2023)
The purpose of this study is to evaluate the cell lines seen on esophagogastoduodenoscopy (EGD) of children who have difficulties feeding, esophageal fistula, and asthma that has some histologic abnormalities. This is a study that looked back at the medical records of 100 children whose cells had been surgically restored after being impacted by EA or TEF. A review of the instrumental tests that were carried out at our facility has been conducted in order to identify any lingering anatomic or functional abnormalities of the airways and gastrointestinal system that would explain the pulmonary clinical images. Due to neurodevelopmental sequelae and the existence of tracheostomies, only 26 sets of pre and post-bronchodilator spirometry data were available for children. 100 children cells with esophageal atresia and tracheoesophageal fistula were included in the study. The average number of weeks spent in gestation was 37.01± 2.33, and the average weight of a newborn was 2614±77.69 grammes. Twenty percent of the children's cells exhibited a syndromic appearance, and the VACTERL connection was identified in seventeen percent of the patients. In all, 80% of the children cells in the sample reported having respiratory symptoms, with 85% of patients experiencing symptoms of the lower respiratory tract and 15% experiencing symptoms of the upper respiratory tract. It is common practice to attribute children's symptoms to reflux and esophageal anomalies, despite the presence of respiratory symptoms and aberrant findings discovered by flexible bronchoscopy and CT assessment.